Synthesis of silica supported bimetallic oxide (NiCo) catalyst for CO2 methanation / Siti Aminah Md Ali - Md Ali, Siti Aminah (2018)
Methane utilisation has been incentivised in recent years as it is less destructive to the environment than other fossil fuels. This research aims to synthesize and optimize nickel based catalysts for the methanation of carbon dioxide to produce methane. The catalysts were prepared in several series designated as 100Ni, 100Co, 90Ni10Co, 10Ni90Co, 100Ni/SiO2, 100Co/SiO2, 90Ni10Co/SiO2, 10Ni90Co/SiO2, 80Ni20Co/SiO2, 60Ni40Co/SiO2, 50Ni50Co/SiO2, 40Ni60Co/SiO2 and 20Ni80Co/SiO2. The supported Ni-Co catalysts were prepared via a reverse co-precipitation method followed by incipient wetness impregnation method. The supported catalyst was synthesised using tetraethylorthosilicate (TEOS) at various metal ratios and calcination over a range of temperatures (300-500°C). Several characterization techniques were applied to understand the chemical and physical properties of the catalysts in order to optimise the catalyst synthesis process. These techniques included N2 adsorption-desorption (BET), Temperature Programmed Reduction (TPR-H2), X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA) and Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX). The highest CO2 conversion obtained using standard reactor parameters was 49.28% (reaction temperature (350°C), GHSV (30,000 mL/gcat.h), reactant ratio H2:CO2 (4:1) for the 80Ni20Co/SiO2 bimetallic catalyst calcined at 500°C. The catalytic performance of the 80Ni20Co/SiO2 catalyst was further optimised in a microactivity reactor where process variables such as temperature (300-500°C), GHSV (15,000 - 75,000 mL/gcat.h) and ratio of reactants of H2: CO2 (2:1-8:1) were varied. The highest C02 conversion obtained was 70.3% at a reaction condition of temperature 400°C, GHSV 15,000 mL/gcat.h and a H2: CO2 reactant ratio of 4:1. The stability of the 80Ni20Co/SiO2 catalyst was also assessed. The catalytic activity was stable across the entirety experiment and produced a CO2 conversion of 67% for 120h at which time testing ceased. The kinetic study discovered that the CH4 and CO formation were described by the zero order reaction with the activation energy of 45.09 and 54.47 kJ/mol respectively. The study concludes that the heterogeneous nickel-based catalyst synthesized successfully catalyzed the methanation of CO2 to produce methane at moderate operating conditions.